Recent trends and reforms in unemployment benefit coverage: the case of employees with non-standard contracts - Berfelde, Mathilde (2020)
The thesis examines the generosity of unemployment benefits granted to non-standard (outsiders) and standard workers (insiders) in four different countries (Germany, the United Kingdom, Italy and Sweden) between 2000 and 2017, which were selected based on their value to represent a different institutional legacy. These legacies were based off the Varieties of Capitalism literature and the Welfare Regime literature. Comparative Case Study Analysis was the chosen methodology to assess the unemployment benefit reforms, which were primarily retrieved from the LABREF database. Two supporting theories were used to analyse the outcomes, dualization theory and liberalization theory. The findings showed a clear correlation between the institutional legacies of each case and the generosity of the unemployment benefits given to insiders and outsiders. The alternative explanation that a common trend towards liberalization made unemployment benefit systems converge in all four countries could not be supported.